2007
DOI: 10.1093/ndt/gfm590
|View full text |Cite
|
Sign up to set email alerts
|

CKD stage-to-stage progression in native and transplant kidney disease

Abstract: Background. Kidney half-life and inter-stage progression rates in native chronic kidney disease (CKD) and CKD-transplant (CKD-T) remain unknown. Methods. We examined stage-to-stage progression/ regression rates in patients with CKD (n ¼ 601) and CKD-T (n ¼ 431) between 1991 and 2001. Kidney function was estimated by Cockcroft-Gault and MDRD eGFR formulae. Kaplan-Meier analyses determined progression and regression half-lives, defined as the time required for 50% of kidneys to advance towards a higher or lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 29 publications
(40 reference statements)
0
34
0
2
Order By: Relevance
“…This infection risk is quite concerning, especially because many patients after allograft failure remain on immunosuppression, including prednisone, calcineurin inhibitors, and/or antiproliferatives. Many studies propose that the CKD staging classification as recommended by KDOQI and Kidney Disease Improving Global Outcomes (KDIGO) and the guidelines for mild, moderate, and severe dysfunction in GFR should also be applied to kidney transplant recipients in the same way as nontransplanted patients (19,(21)(22)(23)(24)(25). Included in these guidelines are the recommendations to place permanent vascular access in stage 4 CKD.…”
Section: Discussionmentioning
confidence: 99%
“…This infection risk is quite concerning, especially because many patients after allograft failure remain on immunosuppression, including prednisone, calcineurin inhibitors, and/or antiproliferatives. Many studies propose that the CKD staging classification as recommended by KDOQI and Kidney Disease Improving Global Outcomes (KDIGO) and the guidelines for mild, moderate, and severe dysfunction in GFR should also be applied to kidney transplant recipients in the same way as nontransplanted patients (19,(21)(22)(23)(24)(25). Included in these guidelines are the recommendations to place permanent vascular access in stage 4 CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The 18th, 58th, 118th, and 155th months' death-censored graft survival probabilities were 0.99, 0.75, 0.25, and 0.10. Kukla and associates 28 found that the deathcensored kidney survival in renal transplant recipients was 1-year 100%, 5-year 89%, and 9-year 50%. Consequently, using estimated GFR-based progression the half-life graft survival was 9.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, chronic allograft dysfunction is characterized by a decline in GFR over time, which in most of the studies can be described by linear or exponential functions. [25][26][27][28][29] We found in many studies, that for data analysis use of the Markov property by modeling the exponential distribution is not unreasonable for multistage disease progression of cancer or chronic disease by Markov assumption. [30][31][32][33] Therefore, we constructed the likelihood function using a time-homogeneous Markov model with a negative exponential waiting time (hereafter called time) in each stage ( Table 1).…”
Section: Statistical Model and Parameters Estimationmentioning
confidence: 99%
“…These patients also experience a number of modifiable conditions that, such as in the case of predialysis patients (PDPs), may carry a high risk of progression to category 5 CKD, cardiovascular events, and death with a functioning graft. 2,3 In most cases, after being exposed to a variable period on dialysis with a resulting endothelial derangement, KTRs may remain under the effect of systemic hypertension, type 2 diabetes mellitus, proteinuria, dyslipidemia, anemia, metabolic acidosis, and secondary hyperparathyroidism. [4][5][6] Because a major concern in follow-up of KTRs includes the alloimmune phenomena, transplant outpatient care may often provide reduced attention to classical clinical factors that favor the progression to CKD, as well as an incomplete clinical approach of CKD-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 To date, a small number of studies have compared the prevalence and quality of treatment of CKD-related complications in KTR and PDP, pointing to a potential role of multidisciplinary clinics in improving CKD management among KTR. 3,9,14 The present study first performed a crosssectional, comparative analyses of the prevalence of CKD-related complications and their clinical management in 2 groups of patients, one consisting of KTRs and the other of PDPs, when both were under multidisciplinary care. The purpose of this study was to evaluate whether a specific treatment for every CKD-related complication was available equally for each group of patients, thus providing supporting evidence in favor of the adoption of multidisciplinary posttransplant clinics.…”
Section: Introductionmentioning
confidence: 99%